Nirbhaya, new media and digital gender activism - Dey, Aja (Digital activism and society., 2018)
Using the 2012 Delhi Nirbhaya rape case as a case study and keeping gender discourses at its core, this book explores the use of digital media for gender activism in India demonstrating how it has formed an alternate platform for dissent.